(untitled) (Gaceta Técnica, 2019)
This paper shows a revision of the text Structural Dynamics Applied to the Seismic Design of Professor Luis Enrique García Reyes, from the Universidad de los Andes, Bogotá, Colombia, in which the most relevant appraisals of its content are collected. Although it has been published in 1998, the subject matter is still valid, and due to the form and sequence in which the contents are presented, it is easy for an undergraduate student in engineering to understand in most of its chapters, being used as text book in the subject Dynamics of Structures of the Universidad Politécnica Salesiana del Ecuador